2020
DOI: 10.3389/fnhum.2020.00281
|View full text |Cite
|
Sign up to set email alerts
|

The Establishment of Pseudorandom Ecological Microexpression Recognition Test (PREMERT) and Its Relevant Resting-State Brain Activity

Abstract: The EMERT (ecological microexpression recognition test) by Zhang et al. (2017) used between-subjects Latin square block design for backgrounds; therefore, participants could not get comparable scores. The current study used within-subject pseudorandom design for backgrounds to improve EMERT to PREMERT (pseudorandom EMERT) and used eyes-closed and eyes-open resting-state functional magnetic resonance imaging to detect relevant brain activity of PREMERT for the first time. The results showed (1) two new recapitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…This further suggests that the specific effects of oxytocin on the recognition of surprised and disgusted micro-expressions may be caused by the effects of oxytocin on insula and amygdala. In fact, previous research on micro-expressions has already found that the recognition accuracy of micro-expressions could be predicted by the resting-state brain activities of insula and amygdala ( Zhang et al, 2020a ). Previous studies also found that oxytocin can affect the facial mimicry process ( Korb et al, 2016 ; Pavarini et al, 2019 ) and the facial mimicry was found to exert its effect on emotion processing through its effect on the neural responses of insula and amygdala (e.g., Lee et al, 2006 ; Rymarczyk et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This further suggests that the specific effects of oxytocin on the recognition of surprised and disgusted micro-expressions may be caused by the effects of oxytocin on insula and amygdala. In fact, previous research on micro-expressions has already found that the recognition accuracy of micro-expressions could be predicted by the resting-state brain activities of insula and amygdala ( Zhang et al, 2020a ). Previous studies also found that oxytocin can affect the facial mimicry process ( Korb et al, 2016 ; Pavarini et al, 2019 ) and the facial mimicry was found to exert its effect on emotion processing through its effect on the neural responses of insula and amygdala (e.g., Lee et al, 2006 ; Rymarczyk et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we employed a laboratory-based paradigm of Japanese and Caucasian Brief Affect Recognition Test (JACBART) to present these micro-expressions ( Matsumoto et al, 2000 ). This well-accepted paradigm presents the micro-expressions in a standardized way which utilizes apparent movement to present the facial dynamics and it can efficiently control the key factors that may moderate the recognition of micro-expressions (e.g., the head movement of the target, the emotion context, the duration and the intensity of micro-expressions; e.g., Matsumoto et al, 2000 ; Ekman, 2009 ; Endres and Laidlaw, 2009 ; Matsumoto and Hwang, 2011 ; Hurley et al, 2014 ; Svetieva and Frank, 2016 ; Demetrioff et al, 2017 ; Felisberti, 2018 ; Zeng et al, 2018 ; Zhang et al, 2020a ). 4 In addition, given that previous studies indicate that the duration of micro-expressions can significantly affect the recognition accuracy of micro-expressions (e.g., Matsumoto et al, 2000 ; Shen et al, 2012 ; Wu et al, 2016 ; Zeng et al, 2018 ; Xie et al, 2019 ), we employed three different settings of duration (i.e., 50, 150, and 333 ms) to test our hypothesis in Study 1.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…It only used the neutral expressions backgrounds before and after a brief microexpression to hide it but did not examine the influence of backgrounds with emotional expressions. The real microexpressions are embedded in the The picture of the experiment procedure from Zhang et al (2020b). These images are licensed by the copyright owners, Tottenham et al (2009) and Zhang et al (2020b).…”
Section: Introductionmentioning
confidence: 99%